Integrating digital marketing in traditional fish processing: Opportunities and challenges - Che Cob, Che Mohd Syaharuddin; Sakarji, Siti Rosnita; Aminuddin, Azwan Shah; Abu Bakar, Hatinah; Nik Man, Nik Faris; Md Apandi, Hassanul Firman (International Journal of Accounting, Finance and Business, 2026)
The integration of digital marketing strategies into traditional fish processing industries represents a critical pathway toward enhancing market competitiveness, expanding customer reach, and improving value-chain efficiency. Despite the growing penetration of digital technologies across agri-food sectors, traditional fish processors, particularly small and medium enterprises (SMEs) face structural, technological, and capability-related constraints that limit digital adoption. This conceptual paper develops a framework that explains how digital marketing integration can transform traditional fish processing businesses by leveraging digital platforms, social media engagement, e-commerce systems, and data-driven marketing. The paper further identifies key opportunities and challenges influencing adoption and proposes a conceptual model linking digital readiness, marketing capability, perceived benefits, and business performance. The study contributes to the literature by bridging digital marketing theory with traditional food processing contexts and offering strategic implications for policymakers, industry stakeholders, and rural entrepreneurs.